Financial literacy and Financial Planning Analysis of Generation Z in Sintang Regency on the Risk of Financial Fraud - Joko Susilo; Yasir Hudzaifah (Journal of Research in Social Science and Humanities, 2025)
This research intends to examine the impact of financial literacy and financial planning on the likelihood of financial fraud among Generation Z in Sintang Regency. The method employed is Partial Least Squares Structural Equation Modeling (PLS-SEM) featuring three primary constructs: financial literacy, financial planning, and risk of financial fraud. The testing results for the outer model indicated that all metrics satisfy the requirements for validity and reliability. The R-square value of 0.946 shows that financial literacy and financial planning account for 94.6% of the variation in the risk of financial fraud. The hypothesis test indicated that financial literacy (? = 0.528; p 0.001) along with financial planning